The identity and typification of two endemic taxa of Carex (Cyperaceae) from Eastern Himalaya - Ghosh, Asok; Mallick, Tanmoy; Majumder, Subrata; Maiti, Gaur Gopal; Naskar, Saikat (Phytotaxa, 2020)
The names Carex crassipes and C. daltoni are lectotypified. The dwarf C. crassipes was considered by Boeckeler as a species different from C. daltoni. However most authors did not recognize its independence, and synonymized it to C. daltoni. We discussed the identity and independence of both taxa using herbarium preserved specimens and recent collection.